1995
DOI: 10.1074/jbc.270.38.22337
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Exchange, Arg-45 to Ala, Generates an Epidermal Growth Factor (EGF) Mutant with High Affinity for the Chicken EGF Receptor

Abstract: The finding that human epidermal growth factor (hEGF) and human transforming growth factor (hTGF) ␣ bind with similar affinity to the human EGF receptor but differ in their affinity for the chicken EGF receptor was used as a model system to study ligand-receptor interaction of EGF receptor agonists. We previously constructed domain-exchange mutants of hEGF and hTGF␣ and found that the region COOH-terminal of the sixth cysteine residue in hTGF␣ is important for high affinity binding to the chicken EGF receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 28 publications
4
51
0
Order By: Relevance
“…The analyses, which used a series of chimeric chicken/human EGFRs, indicated that domain III of the chicken receptor is responsible for this lower affinity to EGF (22). Although structural determinants for the distinct binding properties of the chicken receptor have been investigated in terms of the difference in the primary structure of domain III (32)(33)(34), this could, in part, be explained by the lack of the equivalent sugar chain whose loss leads to the impairment of EGF binding in human EGFR. Nevertheless, the issue of whether the sugar chain is directly associated with the binding currently remains unclear, and it is also possible that the sugar chain may be involved in the correct folding of the domain and/or is required to maintain the conformation of domain III, so that efficient EGF binding can take place.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses, which used a series of chimeric chicken/human EGFRs, indicated that domain III of the chicken receptor is responsible for this lower affinity to EGF (22). Although structural determinants for the distinct binding properties of the chicken receptor have been investigated in terms of the difference in the primary structure of domain III (32)(33)(34), this could, in part, be explained by the lack of the equivalent sugar chain whose loss leads to the impairment of EGF binding in human EGFR. Nevertheless, the issue of whether the sugar chain is directly associated with the binding currently remains unclear, and it is also possible that the sugar chain may be involved in the correct folding of the domain and/or is required to maintain the conformation of domain III, so that efficient EGF binding can take place.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we have shown that chimeras of hEGF and hTGFα, obtained by exchanging domains bordered by their conserved cysteine residues, all have similar binding affinity for ErbB-1 (23). In the nomenclature used, a chimera such as E4T stands for a ligand with hEGF sequences N-terminal and hTGFα sequences C-terminal of the fourth cysteine (19).…”
Section: Erbb-1 Receptor Tyrosine Phosphorylation By Egf/tgfα Chimerasmentioning
confidence: 99%
“…The yield of purified fusion protein was determined in an ELISA-like binding competition on IgG antibodies using biotinlabeled protein A as competitor (22), while the biological activity of the samples was determined in a binding competition assay with iodinated murine (m)EGF on HER-14 cells (23 …”
Section: Ligand Productionmentioning
confidence: 99%
“…T1E not only maintains high affinity for ErbB1, the natural receptor for both EGF and TGF␣, but has in addition gained the ability to bind to ErbB2⅐ErbB3 heterodimers with nearly identical affinity as NRG-1 (26). Subsequent mutation analysis showed that the TGF␣ residues His 4 and Phe 5 in the N terminus and the EGF residue Leu 28 at the tip of the B-loop are essential for the high affinity of T1E for ErbB2⅐ErbB3 heterodimers. Replacement of Leu 28 for the Glu residue present at the equivalent position in TGF␣ strongly impaired binding to ErbB2⅐ErbB3 heterodimers without affecting binding to ErbB1 (26).…”
mentioning
confidence: 99%
“…Subsequent mutation analysis showed that the TGF␣ residues His 4 and Phe 5 in the N terminus and the EGF residue Leu 28 at the tip of the B-loop are essential for the high affinity of T1E for ErbB2⅐ErbB3 heterodimers. Replacement of Leu 28 for the Glu residue present at the equivalent position in TGF␣ strongly impaired binding to ErbB2⅐ErbB3 heterodimers without affecting binding to ErbB1 (26). These results indicated that the combination of residues in the N terminus of TGF␣ and in the B-loop region of EGF mediate the enhanced binding affinity for ErbB2⅐ErbB3 heterodimers.…”
mentioning
confidence: 99%